Reuse of Text in Pali Legal Commentaries - Kieffer-Pulz, Petra (Buddhist Studies Review, 2017)
We will examine three types of reuse represented in Pali legal literature: (1) unacknowledged borrowings of authoritative opinions and definitions adapted (such as by dropping the references given in the source text) and rearranged (Samantapasadika > Kankhavitarani; fourth to fifth century ce); (2) unacknowledged borrowings of largely unchanged selected text portions being rearranged (Samantapasadika > Vinaya-sangaha; twelfth century CE); and (3) unconnected extracts of unchanged text portions lined up in the sequence of the source text (for instance Patimokkha-padattha-anuvannana > Vinaya-lakkhana-rasi; eighteenth (?) century CE).